Effects on child growth of a reduction in the general food distribution ration and provision of small-quantity lipid-based nutrient supplements in refugee camps in eastern Chad. Issue 1 (14th May 2021) - Fenn, Bridget; Myatt, Mark; Mates, Emily; Black, Robert E; Wilkinson, Caroline; Khara, Tanya
Abstract : Background: We used the United Nations High Commissioner for Refugees Standardised Expanded Nutrition Survey data to evaluate the effect of a change in food ration on child growth in refugee camps in eastern Chad. Methods: We compared trends of wasting and stunting prevalence over time and the association between the coexistence of being both stunted and wasted using Pearson's χ 2 test. We analysed the effect of an approximate 50% reduction in the general food distribution, with the introduction of a 20 g daily ration of small quantity lipid-based nutrient supplements given to all children aged 6–23 months, on child growth. This was done using interrupted time-series analysis to observe differences in levels and trends in mean height-for-age z-score (HAZ) and weight-for-height z-score (WHZ) over time and by age group (6–24 months and 24–59 months). Results: Overall the prevalence of stunting and wasting decreased significantly over time. The odds of being both stunted and wasted was 1.38 higher than having one or the other condition separately (p<0.001, 95% CI=1.29 to 1.47). Trends in mean HAZ and WHZ before and after a ration change in 2014 indicate that growth had either slowed down or worsened. In the period following the ration change, children 24–59 months saw a significant decrease in mean HAZ of 0.04 per year (p=0.02, 95% CI=−0.07 to –0.01) and for the younger age group, there was a significant decrease in mean WHZ of 0.06 per year (p=0.03, 95% CI=−0.12 to –0.01). Conclusions: The dual burden of stunting and wasting is a considerable challenge in refugee camp settings. Changes to the food distribution had adverse effects on child growth for both age groups. Broadening the scope of interventions aimed at children in camps is essential when tackling malnutrition with increased efforts essential during periods of wider food assistance shortages.